2022
DOI: 10.1029/2021jd035213
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Aerosol Diversity Over the Northern South China Sea: The Influence of Land and Ocean

Abstract: Fungal aerosols are ubiquitous in the atmosphere and can directly and/or indirectly affect the atmospheric cloud formation process, which play an important role in global climate change and human health. In this study, we performed a comprehensive study on airborne fungi over the northern South China Sea (NSCS). Total suspended particle (TSP) samples were collected during a cruise campaign in the NSCS, and fungal community structure was obtained via high‐throughput sequencing method. The abundance of Ascomycot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Fungal aerosols are ubiquitous in the atmosphere and play an important role in global climate change and human and nonhuman animal health (e.g., Aspergillus fumigatus ), and the size distribution and concentration of fungal aerosols are key for infection of the host [ 36 , 37 , 38 , 39 , 40 , 41 ]. Airborne transmission has also been considered an important mode for the epidemiology of plant fungal disease, in addition to water, insects, and animals, for dispersal of their spores, e.g., in Corynespora cassiicola , Alternaria alternate , and P. graminis f.sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungal aerosols are ubiquitous in the atmosphere and play an important role in global climate change and human and nonhuman animal health (e.g., Aspergillus fumigatus ), and the size distribution and concentration of fungal aerosols are key for infection of the host [ 36 , 37 , 38 , 39 , 40 , 41 ]. Airborne transmission has also been considered an important mode for the epidemiology of plant fungal disease, in addition to water, insects, and animals, for dispersal of their spores, e.g., in Corynespora cassiicola , Alternaria alternate , and P. graminis f.sp.…”
Section: Discussionmentioning
confidence: 99%
“…The size of bioaerosols is a main factor that impacts their ability to reach plant tissues through natural openings and successfully infect host plants [ 21 ]. Previous studies showed that the size distributions of airborne fungi ranged from 0.65 µm to larger than 7 µm [ 39 , 47 ]. In our study, approximately 38% of B. cinerea aerosols were distributed in the 1.1–2.1 μm range, and particle sizes of 4.7–7.0 µm were the least frequent (accounting for 7.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Soil and leaves were identified as potential natural sources of airborne fungi (Qi et al., 2020). The structure of fungal communities may be influenced during transportation by both terrestrial and oceanic air mass (Shi et al., 2022), for example, Nigrospora and Cladosporium serve as potential indicators of terrestrial fungal aerosols in the South China Sea. Fungal spores play a crucial role as allergenic components in particulate matter from local emission or long‐range transport.…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms thrive in a variety of aquatic and terrestrial environments and knowledge of their sources and potential contribution to the global climate budget has received considerable attention (Jaenicke, 2005, Mayol et al, 2017Shi et al, 2022). Notes of airborne transport of microorganisms are dated back to early days of discovering microorganisms (Gregory, 1971;Gorbushina et al, 2007).…”
Section: Introductionmentioning
confidence: 99%